Propuesta de mejora en la bodega de no perecibles en una empresa de distribución de alimentos en la ciudad de Quito - Chafuelan Amaguaña, Katherine Alejandra (2024)
The objective of this project is to develop an improvement proposal to optimize the operations of the non-perishable products warehouse of a food distribution company in the city of Quito. Different tools are applied to increase efficiency, quality and customer satisfaction. The study addresses the current situation of the warehouse, identifying inefficiencies in the distribution of spaces, picking processes, storage and inventory management. The PDCA cycle is used to propose strategies to optimize the flow of materials and personnel, standardize processes and eliminate waste. The research is based on a bibliographic review and a field study in the company, collecting data that allow diagnosing and validating the improvement proposal. The expected results include improved operational efficiency, product quality and customer satisfaction, offering a reference for other companies in the food sector that face similar challenges.